Consuming desire the commodification of male body transformation journeys on Instagram - Caasi, Damiel Joseph Umali
This study examined the concept of desire and male body transformation journey by following Graham's (2007) theory of Political Economy of Communication. It utilized a collective study of six male fitness influencers or fitsfluencers who shared their body transformation stories on Instagram. The interviews and accompanying visuals were analyzed using thematic and textual analysis. The findings of the study formed the "Treadmill" framework, which illustrates the concept of desire and body transformation among the participants. The framework consists of three stages: warm-up, work-out and cool down. The study suggests that there are political-economic implications that influence the desires of male fitsfluencers on Instagram to attain their desired physique and its connection to consumer culture.